SPEECH AND LANGUAGE COMPETENCES OF PERSONALITY: THEORETICAL AND PSYCHOLOGICAL PROJECTION: competence; key competences; expertise; language competence; speech competence - Vlasenko, Olena (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The article presents theoretical approaches to the definition of language competence and speech competence. It reveals general properties of these phenomena and the author's approach to the definition of these notions. The aim of the research is the theoretical study of psychology of the development of language competence and speech competence concepts, as well as the description of the author’s approach to the definition of these notions. The goal is extrapolated to the need for theoretical substantiation of the author's approach to the definition of these concepts. One highlights the development process of these phenomena and determines the general properties of concepts, their interaction and interdependence. The article analyzes the correlation of such concepts as key competencies, competence and expertise. The research procedure involved the use of methods of analysis and synthesis, induction and deduction, in order to explain the author's approach to the definition of language competence and speech competence. This methodology allowed determining the main approaches of other scientists to these definitions. It is found that the above-mentioed definitions of the studied notions have common properties. One determines that language and speech competencies are interrelated as part and whole. The result of the study was the statement of the general properties of language competence and speech competence phenomena, as well as the explanation of the author's approach to the definition of these notions. The conclusions summarize the general properties of the definitions of language competence and speech competence. The author's definition of these concepts is described. One concludes that language and speech competencies are interrelated, and one is part of the other